Identification and testing of novel CARP-1 functional mimetic compounds as inhibitors of non-small cell lung and triple negative breast cancers - Muthu, Magesh; Somagoni, Jaganmohan; Cheriyan, Vino T.; Munie, Sara; Levi, Edi; Ashour, Abdelkader Elbadawy Abbas; Yassin, Alaa Eldeen B.; Alafeefy, Ahmed M.; Sochacki, Paula; Polin, Lisa A.; Reddy, Kaladhar B.; Larsen, Scott D.; et al. (American Scientific Publishers, 2015)
The triple negative breast cancer (TNBCs) and non-small cell lung cancers (NSCLCs) often acquire mutations that contribute to failure of drugs in clinic and poor prognosis, thus presenting an urgent need to develop new and improved therapeutic modalities. Here we report that CARP-1 functional mimetic (CFMs) compounds 4 and 5, and 4.6, a structurally related analog of CFM-4, are potent inhibitors of TNBC and NSCLC cells in vitro. Cell growth suppression by CFM-4 and -4.6 involved interaction and elevated expression of CARP-1/CCAR1 and Death Effector Domain (DED) containing DNA binding (DEDD)2 proteins. Apoptosis by these compounds also involved activation of pro-apoptotic stress-activated kinases p38 and JNK1/2, cleavage of PARP and loss of mitotic cyclin B1. Both the CFMs inhibited abilities of NSCLC and TNBC cells to migrate, invade, and form colonies in suspension, while disrupting tubule formation by the human umbilical vein endothelial cells (HUVECs). Nano-lipid formulation of CFM-4 (CFM-4 NLF) enhanced its serum bioavailability when compared with the free CFM-4. Oral administration of CFM-4 NLF reduced weights and volume of the xenografted tumors derived from A549 NSCLC and MDA-MB-231 TNBC cells. Although no gross tissue or histological toxicities were noticed, the immuno-histochemical analysis revealed increased CARP-1 and DNA fragmentation in tumors of the CFM-4 NLF-treated animals. In conclusion, while stimulation of pro-apoptotic CARP-1 and DEDD2 expression and their binding underscore a novel mechanism of apoptosis transduction by CFM compounds, our proof-of-concept xenograft studies demonstrate therapeutic potential of CFM-4 for TNBC and NSCLC.